Pengaruh Kualitas Produk, Brand Image Dan Brand Ambassador Terhadap Keputusan Pembelian Kosmetik Madame Gie Pada Mahasiswa Di Kota Bandung - Putri, Ariel Anggistia; Herlina, Listri; Kusumawardani, Astrin (Journal of Information System, Applied, Management, Accounting and Research, 2025)
This study aims to examine the influence of product quality, brand image, and brand ambassadors on consumer purchasing decisions for Madame Gie products in Bandung City. A quantitative research method with descriptive and verification approaches is employed. The sampling technique used is probability sampling, where respondents are selected randomly from accessible customers. Data are analyzed using path analysis to determine the relationships among the studied variables. The findings indicate that product quality, brand image, and brand ambassadors each have a significant and positive effect on consumer purchasing decisions. Among these factors, brand image exerts the strongest influence on customer perceptions, while product quality and brand ambassadors play crucial roles in enhancing consumer purchase intention. Therefore, companies should reinforce their brand image, enhance product quality, and strategically select brand ambassadors to foster customer loyaltyThis study aims to examine the influence of product quality, brand image, and brand ambassadors on consumer purchasing decisions for Madame Gie products in Bandung City. The analysis is conducted both partially (individually) and simultaneously (collectively). A quantitative research method with descriptive and verification approaches is employed. The sampling technique used is probability sampling, where respondents are selected randomly from accessible customers. Data are analyzed using path analysis to determine the relationships among the studied variables. The findings indicate that product quality, brand image, and brand ambassadors each have a significant and positive effect on consumer purchasing decisions. Among these factors, brand image exerts the strongest influence on customer perceptions, while product quality and brand ambassadors play crucial roles in enhancing consumer purchase intention. Therefore, companies should reinforce their brand image, enhance product quality, and strategically select brand ambassadors to foster customer loyalty.